2018
DOI: 10.1101/272351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ratiometric assays of autophagic flux in zebrafish for analysis of familial Alzheimer’s disease-like mutations

Abstract: Protein aggregates such as those formed in neurodegenerative diseases can be degraded via autophagy. To assess changes in autophagic flux in zebrafish models of familial Alzheimer’s disease (fAD) mutations, we first developed a transgene, polyQ80-GFP-v2A-GFP, expressing equimolar amounts of aggregating polyQ80-GFP and a free GFP internal control in zebrafish embryos and larvae. This assay detects changes in autophagic flux by comparing the relative strength of polyQ80-GFP and free GFP moiety signals on western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…not the endoproteolytically-cleaved, γ-secretase-active form of PSEN1) was required for normal acidification of lysosomes by promoting N-glycosylation of the V0a1 subunit of v-ATPase that is required for its correct localization to the lysosome. (Note that it has not yet been demonstrated formally that PSEN2 plays a similar role although, in work yet to be published formally, we claim that homozygosity for psen2 S4Ter causes decreased autophagic flux in zebrafish larvae [67]). Recently, Yambire et al demonstrated that deficient lysosomal acidification causes a cellular deficiency of ferrous iron leading to brain mitochondrial dysfunction and inflammatory responses [68].…”
Section: Plos Onementioning
confidence: 66%
“…not the endoproteolytically-cleaved, γ-secretase-active form of PSEN1) was required for normal acidification of lysosomes by promoting N-glycosylation of the V0a1 subunit of v-ATPase that is required for its correct localization to the lysosome. (Note that it has not yet been demonstrated formally that PSEN2 plays a similar role although, in work yet to be published formally, we claim that homozygosity for psen2 S4Ter causes decreased autophagic flux in zebrafish larvae [67]). Recently, Yambire et al demonstrated that deficient lysosomal acidification causes a cellular deficiency of ferrous iron leading to brain mitochondrial dysfunction and inflammatory responses [68].…”
Section: Plos Onementioning
confidence: 66%